UJI PATOGENISITAS DAN IDENTIFIKASI CENDAWAN PENYEBAB BUSUK AKAR PADA POHON KETAPANG KENCANA (Terminalia mantaly) - Alam, Muhammad; Firmansyah, Firmansyah; Taufiqurrozif, Hafiz; Basrudin, Basrudin (Lambung Mangkurat University-Indonesia, 2024)
Root rot disease attacks various types of forest plants, such as albizia, acacia, agathis, and pine. Root rot attack was also found in ketapang Kencana trees which caused the collapse of the tree and harmed the people around it. This study aims to test the pathogenicity and identify the type of fungus that causes root rot disease in ketapang Kencana plants. The research method included pathogenicity testing by inoculating fungal isolates and identification of species using morphological characteristics of the fungus. The fungus that was identified was Fusarium sp. and Botryodiplodia sp.. Botryodiplodia sp. identified as a pathogenic fungus that is suspected of causing root and stem rot symptoms in ketapang kencana plants because it caused an attack on the test sample in the form of albizia wood. Botryodiplodia sp. isolate has macroscopic characteristics of white colonies which then turn gray, with a texture resembling cotton, and has microscopic characteristics of verticillate conidiophores, oval conidia with two tapered ends, hyaline hyphae which later turn dark.